Predominant Promotion by Tacrolimus of Chondrogenic Differentiation to Proliferating Chondrocytes - Yukari Nakamura; Takeshi Takarada; Ayumi Kodama; Eiichi Hinoi; Yukio Yoneda (Elsevier, 2009)
Tacrolimus (FK506) has been used as a therapeutic drug beneficial for the treatment of rheumatoid arthritis in humans. In this study, we investigated the effects of FK506 on cellular differentiation in cultured chondrogenic cells. Culture with FK506 led to a significant and concentration-dependent increase in Alcian blue staining for matrix proteoglycan at 0.1 to 1,000 ng/ml, but not in alkaline phosphatase (ALP) activity, in ATDC5 cells, a mouse prechondrogenic cell line, cultured for 7 to 28 days, while the non-steroidal anti-inflammatory drug indomethacin significantly decreased Alcian blue staining in a concentration-dependent manner, without altering ALP activity. FK506 significantly increased the expression of mRNA for both type II and type X collagen, but not for osteopontin, in ATDC5 cells. Similar promotion was seen in chondrogenic differentiation in both mouse metatarsals and chondrocytes cultured with FK506. However, FK506 failed to significantly affect transcriptional activity of the reporter construct for either sry-type HMG box 9 (Sox9) or runt-related transcription factor-2 (Runx2), which are both transcription factors responsible for chondrocytic maturation as a master regulator. These results suggest that FK506 may predominantly promote cellular differentiation into proliferating chondrocytes through a mechanism not relevant to the transactivation by either Sox9 or Runx2 in chondrogenic cells. Keywords:: tacrolimus, ATDC5 cell, metatarsal, chondrocyte, type II collagen